INDUSTRIAL RELATIONS: COMPARATIVE NON-STANDARD EMPLOYMENT RELATIONSHIP IN NIGERIA AND INDONESIA - Devi Melisa Damiri; Mohammad Benny Alexandri (Departemen Ilmu Administrasi Bisnis, Fakultas Ilmu Sosial dan Ilmu Politik, UNPAD, 2017)
ABSTRACTThe research objective is to study and determine the level of non-standard employment relationships in Nigeria and Indonesia. The employment relationship is not as standard as is initial workers, which are contract employees and outsourcing. The nonstandard employment relationship are reinforced by the number of unemployment in Nigeria and Indonesia which are every form of nonstandard employment will offer the challenge but it will tend to have the great of losses.The results of the study found that non-standard employment relationships in Nigeria and Indonesia in general is not different. Most employees are not standard work is in positions which have low skills, without a career path and can harm the development of human resources for both companies or clients. On the other hand, who had a temporary job as an employee or non-standard employee is better than not having a job. Therefore the unemployment rate can be reduced and can significantly increase the country's economic growth.Keywords: Unemployement, nonstandard employment relations, contract employees, outsourcing, country’s economic growth HUBUNGAN INDUSTRIAL: PERBANDINGAN HUBUNGAN KERJA TIDAK STANDAR DI NEGARA NIGERIA DAN INDONESIA ABSTRAKPenelitian ini bertujuan untuk mempelajari dan menentukan tingkat hubungan kerja tidak standar di Nigeria dan Indonesia. Hubungan kerja tidak standar yang dimaksud sebagai karyawan kontrak dan outsourcing. Hubungan kerja tidak standar diperkuat oleh jumlah pengangguran yang ada di Nigeria dan Indonesia dimana setiap bentuk pekerjaan tidak standar menawarkan tantangan namun akan cenderung memiliki banyak kerugian. Hasil penelitian ditemukan bahwa hubungan kerja tidak standar di Nigeria dan Indonesia pada umumnya tidak berbeda. Sebagian besar karyawan merupakan pekerja tidak standar yang memiliki keterampilan kerja yang rendah, tanpa memiliki jenjang karir dan dapat membahayakan perkembangan sumber daya manusia baik bagi perusahaan maupun klien. Di sisi lain, memiliki pekerjaan sementara baik sebagai pekerja standar ataupun pekerja tidak standar akan lebih baik daripada tidak memiliki pekerjaan. Dengan demikian tingkat pengangguran dapat dikurangi dan secara signifikan dapat meningkatkan pertumbuhan ekonomi negara.Kata kunci: Pengangguran, hubungan kerja tidak standar, karyawan kontrak, outsourcing, pertumbuhan ekonomi negara.